A Spectrum of Changes Occurs in Peptidoglycan Composition of Glycopeptide-Intermediate Clinical Staphylococcus aureus Isolates - Boyle-Vavra, Susan (American Society for Microbiology, 2001)
The mechanism of glycopeptide resistance in Staphylococcus aureus is not known with certainty. Because the target of vancomycin is the d-Ala–d-Ala terminus of the stem peptide of the peptidoglycan precursor, by subjecting muropeptides to reversed-phase high-performance liquid chromatography, we investigated peptidoglycan obtained from glycopeptide-intermediate S. aureus (GISA) isolates for changes in composition and evaluated whether any peptidoglycan structural change was a consistent feature of clinical GISA isolates. GISA isolates Mu50 and Mu3 from Japan had the large glutamate-containing monomeric peak demonstrated previously, although strain H1, a vancomycin-susceptible MRSA isolate from Japan that was clonally related to Mu3 and Mu50, and a femC mutant that we studied, did also. For the U.S. GISA isolates, strain NJ had a large monomeric peak with a retention time identical to that described for the glutamate-containing monomer in strains H1, Mu3, and Mu50. However, a much smaller corresponding peak was seen in GISA MI, and this peak was absent from both GISA PC and a recent GISA isolate obtained from an adult patient in Illinois (strain IL). These data suggest that a uniform alteration in peptidoglycan composition cannot be discerned among the GISA isolates and indicate that a single genetic or biochemical change is unlikely to account for the glycopeptide resistance phenotype in the clinical GISA isolates observed to date. Furthermore, a large monomeric glutamate-containing peak is not sufficient to confer the resistance phenotype.